2022
DOI: 10.48550/arxiv.2206.03057
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficient Dust Radial Drift Around Young Intermediate-mass Stars

Paola Pinilla,
Antonio Garufi,
Matías Gárate

Abstract: The radial velocities and direct imaging observations of exoplanets have suggested that the frequency of giant planets may decrease for intermediate-mass stars (2.5 − 8 M ). The key mechanism that could hinder their formation remains unclear. From a theoretical point of view, planet formation around intermediate-mass stars may take place on longer timescales, which -coupled with fast migration and efficient photoevaporation -may prevent planetary formation in these environments. In this letter, we investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…It has been demonstrated that these radial drift velocities are higher for disks around BDs and VLMS [32,63]. This is because the radial drift velocities of dust particles depend on the stellar mass and luminosity as v drift ∝ L 1/4 / √ M , where the dependency with stellar mass dominates for the low mass regime, while the stellar luminosity dominates for intermediate-mass stars M > 2.5M [65]. Figure 4 shows the stellar evolution up to 30 Myr of 0.1-1 M stars in the H-R diagram (left panel) and the absolute value of the maximum drift velocity as a function of time of dust particles around a 0.1 M and 1 M .…”
Section: Radial Drift Around Bds and Vlmsmentioning
confidence: 99%
“…It has been demonstrated that these radial drift velocities are higher for disks around BDs and VLMS [32,63]. This is because the radial drift velocities of dust particles depend on the stellar mass and luminosity as v drift ∝ L 1/4 / √ M , where the dependency with stellar mass dominates for the low mass regime, while the stellar luminosity dominates for intermediate-mass stars M > 2.5M [65]. Figure 4 shows the stellar evolution up to 30 Myr of 0.1-1 M stars in the H-R diagram (left panel) and the absolute value of the maximum drift velocity as a function of time of dust particles around a 0.1 M and 1 M .…”
Section: Radial Drift Around Bds and Vlmsmentioning
confidence: 99%